Preparation of insulating material based on rice straw and inexpensive polymers for different roofs - Nasser, Reem; A. Radwan, M.; A.Sadek, M.; A.Elazab, Hany (International Journal of Engineering and Technology, 2018)
Fossil fuel saving is part of the 21th century goal. One of the largest sectors that consumes energy is the building sector since it consumes 40% of the total energy in Europe through heating and cooling. Thus, the need of minimizing the energy consumption played an important role in the development of building insulation materials.Â Selection of a proper material for building insulation differs according to the building surrounding climate and the properties required in the material. Building climate determines the insulating material location whether its internal or external while properties can differ according to many parameters that affect the material quality such as thermal insulation, acoustic insulation, waterproofing, resistance to fire and mechanical properties. Another factor is newly considered which doesnâ€™t affect the product quality but has an influence in the energy consumption is the environmental impact.Â The aim of the research is considering most of the above factors through making a composite of rice straw particles bounded by a polymer to produce roof insulations. The utilization of wastes such as rice straw to produce a high quality product with the least price is the research main objective. The polymers selected for research are the unsaturated polyester resin and the polyurethane foam polymers. The polyester is not recently applied for insulation on comparison with the polyurethane foam which is dominant through the global market.Â At the end of the research, satisfying results have been achieved to nominate the 80% polyurethane foam and 20% rice straw composite as the best sample among all of the prepared samples. The other samples include polyester and rice straw composite with different compositions. The foam and straw sample have the best insulation with value of 0.1627 W/m oC. The compression strength has also been improved on addition of rice straw to the polyurethane foam by three times the initial value. Also, the density measurement revealed a very light composite which is suitable for the construction field requirements. This results in reducing the cost by 28.35%. On contrast, polyester samples which have very high density and higher K factor are not so efficient, so it is suggested that they can be applied at rural regions due to their low cost.Â Â